COOPERATION BETWEEN SPEECH AND LANGUGAGE THERAPIST AND FAMILY TO PROMOTE READING SKILLS IN FIRST GRADE PUPILS - Tūbele, Sarmīte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Reading skills are one of essential skills to acquire literacy and be successful in everyday life in school and after it. Literacy skills are complicated for pupils with speech and language disorders, it is responsibility not only of speech and language therapists, but also of family to help these children to become literate. Situation in Latvia is different in different educational institutions, but we have to try our best to involve parents/family to be a part of pupil’s everyday activities.The aim of the article is to state the necessity of cooperation and to explore what kind of cooperation is effective in acquiring reading skills in first grade pupils. Based on the scientific literature theoretical framework is updated and method of questionnaire is used, analysis of the collected data is presented. Main conclusions – cooperation with family improve the results of acquiring reading skills in the first grade pupils with speech and language disorders and promote the reading interest